Consider the below recurrence(adsbygoogle = window.adsbygoogle || []).push({});

##T(n) = 2 T(\sqrt(n)) + \log n##

substituting ##\log n = m \implies n = 2^m##

##T(2^m) = 2 T(2^{\frac{m}{2}}) + m##

substituting ##S(k) = T(2^m)## I'm getting below equation

##S(k) = 2 S(\frac{k}{2}) + m##

How can I change 'm' to 'k' in above equation.

**Physics Forums - The Fusion of Science and Community**

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Solving recurrence by changing variables

Loading...

Similar Threads - Solving recurrence changing | Date |
---|---|

Changing Algorithms compatible with AI? | Oct 16, 2017 |

C/++/# Simple bisection program - solved | Apr 12, 2017 |

Solving partial differential equation numerically | Dec 19, 2016 |

Solving differential equations using numeric methods | Oct 26, 2016 |

Python Testing code to solve 2nd order wave equation | Oct 8, 2016 |

**Physics Forums - The Fusion of Science and Community**